Interpreting Sufi Ethical Frameworks for Counseling Practice: A Hermeneutic Analysis of Abah Anom’s Teachings - Ishlakhatus Sa'idah; Najlatun Naqiyah; Titin Indah Pratiwi; Ari Khusumadewi (KONSELOR, 2026)
Counselling ethics has been predominantly shaped by Western philosophical traditions, yet its application in culturally diverse settings requires ethical grounding that resonates with local moral understandings. Rather than assuming limitations in international codes, this study examines how a contextualised ethical perspective may complement existing frameworks by exploring the teachings of Abah Anom, a widely respected Sufi guide whose ethical reflections remain influential within Indonesian Muslim communities. His teachings are analysed not as theological prescriptions but as culturally situated ethical resources that illuminate intention, emotional discipline, relational presence, and moral orientation in counselling practice. The study employs a Gadamerian hermeneutic approach, drawing on textual sources, including Miftahus Shudur, sermon transcripts, and institutional documents, and purposively selected informants comprising senior disciples, a Sufi scholar, and counsellors familiar with his teachings. The analytic process followed an iterative part-whole movement, dialogical interpretation, and socio-religious contextualisation to construct meaning across texts, participant experiences, and contemporary counselling concerns. The analysis identifies four ethical dispositions: sincerity, patience, empathy, and service, as dynamic modes of ethical self-formation rather than fixed moral virtues. These dispositions guide counsellors in aligning intention with client welfare, regulating affective responses, deepening relational understanding, and maintaining an orientation of service towards others. A key interpretative insight that emerged is the view of ethical practice as an ongoing cultivation of inner states, offering an alternative perspective to procedural or rule-based approaches commonly emphasised in professional codes. The study contributes by showing how a local Sufi moral framework can enter into constructive dialogue with global counselling ethics and enrich culturally responsive practice without proposing doctrinal authority or universal applicability. Future research may focus on how these ethical dispositions are enacted in real counselling interactions or undertake comparative hermeneutic studies across other Indonesian spiritual traditions.